I defintely didn't do this in a smart way, but a more complicated manner.

First, let's put s in terms of t so we can do some subsitutions. We get

\(s=-\frac{2\left(-4t+1\right)}{5}\) from the first equation.

Subsituting this value of s into the second equation, we get

\(3t-6\left(-\frac{2\left(-4t+1\right)}{5}\right)=9-2t\)

Now, we solve for t. We get

\(\frac{-23t+12}{5}=9\\-23t+12=45\\t=-\frac{33}{23}\)

Now, we subsitute t back into the first equation to find s. We get

\(s=-\frac{62}{23}\)

Thus, we finally find the ordered pair as

\(s=-\frac{62}{23},\:t=-\frac{33}{23}\)

So our final answer is \((-62/23, -33/23)\)

Thanks! :)